If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67 + -20 = 2y + -4 Combine like terms: 67 + -20 = 47 47 = 2y + -4 Reorder the terms: 47 = -4 + 2y Solving 47 = -4 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 47 + -2y = -4 + 2y + -2y Combine like terms: 2y + -2y = 0 47 + -2y = -4 + 0 47 + -2y = -4 Add '-47' to each side of the equation. 47 + -47 + -2y = -4 + -47 Combine like terms: 47 + -47 = 0 0 + -2y = -4 + -47 -2y = -4 + -47 Combine like terms: -4 + -47 = -51 -2y = -51 Divide each side by '-2'. y = 25.5 Simplifying y = 25.5
| 4x(2+2)+4*6= | | 6y^2+28y-98=0 | | 3p-7=2(4-p) | | 5.6=10x+6.1 | | fx=3(2x-1) | | X/8+4=6 | | 1/4(8x-20)=1/3(15x-6) | | (3-7j)+(9-j)= | | Y-6.8=8 | | 2.5x+9-4.5x=1 | | 6-(6-10*343)= | | 9i/(8-5i) | | 5x-37.6=x | | x^2+16*x+1.2=0 | | 4(y+5)=32 | | 6m=2(5m+10) | | 0.5x+0.6=-1.9 | | [2(4-7)]= | | 3(2g+7)-6g-21=0 | | (x^4-y^4)*(x^4+y^4)=0 | | 2(x-8.8)=4.6 | | -12=4-21 | | 14x+93=261 | | 8=3x+4(-2x) | | 13-2(3x-6)=2(2-4x) | | 7x+5.03=4x+11 | | (x+3)*(x-4)=0 | | 43-1296-125= | | 9.9a+9.63=-88.38 | | y=1.2-3+3 | | y=1.3-3+3 | | 10-7x=50-42x |